Application of surface brachytherapy in treatment of classic Kaposi's sarcoma relapse - E. v Sokolovskiy; G. N. Mikheev; V. V. Iastrebov; A. P. Litvinov; A. V. Shcherbatykh; V. A. Seredina (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The authors describe a patient of 63 years with a classic Kaposi's sarcoma relapse, having contraindi - cations for cytostatic therapy. They also present literature data concerning the etiology, pathogenesis, diagnosis and treatment of disease.